ANALISIS WILAYAH KOMODITAS UBI KAYU DAN KONTRIBUSINYA TERHADAP SEKTOR PERTANIAN DI KABUPATEN PACITAN - Ainun Faidah; Triana Dewi Hapsari; Jani Januar (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2016)
Pacitan Regency is the second highest cassava producing area in East Java Province, our production mean 468.326 ton at period 2011-2013. The objectives of this research are to know: (1) the production basis districts of cassava commodity in Pacitan Regency, (2) the spreading characteristics of cassava commodity in Pacitan Regency, (3) the contribution of cassava commodity to the GDP of food crops subsector and the agricultural sector in Pacitan Regency. The research was deliberately condusted in Pacitan Regency, East Java Province. The descriptive and analytical methods are applied in this research. The data used is secondary data with main data sources are BPS Pacitan Regency. Data analysis tools used are Location Quotient (LQ), localization coefficient and specialization coefficient analysis and contributions. The results showed that: (1) the production basis districts area of cassava commodity in Pacitan Regency during 2008-2013 are the district; Tulakan, Pringkuku, Tegalombo, and Sudimoro (2) the spreading characteristics of agricultural activities of cassava commodity in Pacitan Regency was not localized and Pacitan Regency does not specialize its agricultural activities on cassava commodity, (3) the contribution of cassava commodity to the GDP of food crops and agricultural sector in Pacitan Regency is low.